Metaphor Depicted in Taylor Swift's Songs - Dea Salsabila; Indah Damayanti; Adelia Puspa (Universitas Bengkulu, 2025)
A metaphor is a figure of speech or figurative language used to make an indirect comparison between two different things. Metaphors can be found in various media, including song lyrics. This research aims to determine the types of metaphors and their meanings in Taylor Swift's album